Impact of Leadership Approach on Employee Motivation in Multi-Cultural IT Companies - Dhavala, Kiran Mayee (Digital Repository of Theses, 2025)
Annually, various organizations publish rankings of top employers, and corporations strive to be included in these lists. Employees seek positions at such companies, while executives aim to manage their organizations effectively, prioritizing worker contentment. The IT industry has experienced substantial expansion in recent years. In this environment, comprehending how leadership influences employee job satisfaction is vital for organizational achievement. This investigation examines the connection between leadership approaches and job contentment in small North American IT firms with international operations. The research employs a hybrid methodology, utilizing both surveys and interviews to collect data from employees in these companies. Quantitative survey analysis will determine the frequency of various leadership styles, while qualitative interviews will provide detailed insights into their effects on job satisfaction. The study has three aims: to examine prevalent leadership methods in small North American IT businesses with global reach, assess how these approaches impact job satisfaction, and identify leadership qualities that significantly boost employee contentment in a global setting. The research outcomes are anticipated to offer practical guidance for leaders of small IT enterprises seeking to implement effective leadership strategies that enhance job satisfaction on a global scale. Additionally, the study will contribute to the existing knowledge base on leadership and job satisfaction in the IT sector, providing direction for improving organizational efficacy and employee well-being. Ultimately, this research underscores the significance of effective leadership in small IT businesses with international operations, emphasizing job satisfaction as a crucial factor for success in today's competitive IT landscape.